Implementasi Pembelajaran Audio Visual Terhadap Hasil Belajar Siswa Kelas V SDN Poma, Kecamatan Kota Tambolaka, Kabupaten Sumba Barat Daya Propinsi Nusa Tenggara Timur - Daindo Milla (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2021)
This study aims to determine the effect of using audio-visual learning media on the learning outcomes of fifth grade students at SDN Poma, Kec. Tambolaka City, Kab. Sumba Barat Daya, NTT Province in the Science Subject material on how the body processes clean air. This type of research is a Quazi Experiment Design type of Non-Equivalent Control Group Design. The method used is to give a pre-test first without choosing randomly both the control class and the experimental class so that the results of the treatment can be known more accurately. The research subjects were all fifth grade students of SDN Poma. The data collection technique used a test technique which was analyzed using the SPSS for windows 20 computer program. Based on the results of the research and the results of data analysis, the value of 8,390 > t table 2,021 showed that audio-visual media had an effect on the learning outcomes of fifth graders at SDN Poma in the Natural Sciences subject. Treating Clean Air. Based on the results of the overall discussion, it can be concluded that audio-visual media affects the learning outcomes of fifth graders at SDN Poma with a sig value of 0.000 <0.05 as the basis for making the decision on the hypothesis that H1 is accepted and H0 is rejected and states that there is an influence between the independent variable (X) on the dependent variable (Y) under study. Keywords: Learning Outcomes, Audio Visual Learning Media